Professional Quality of Life and Its Association with Work Experience and Income among Healthcare Worker - Nirmeen Maroof; Mirza Zeeshan Sikandar; Haleema Nawaz; Syed Imran Ali Shah (Aziz Fatimah Medical and Dental College, 2019)
Objective: The objective of the study is to assess job satisfaction between groups of healthcare workers based on their work experience and monthly salary. Methodology: Healthcare workers (n=81) including clinicians, nurses and medical teachers were recruited from a private medical institute at Lahore. Job Satisfaction Survey (JSS) and Professional Quality of Life (ProQOL) Scale including its component scales of Compassion Satisfaction (CS), Burnout (BO) and Secondary Traumatic Stress (STS) were used to determine aspects of vocational quality of life and satisfaction. Kruskal-Wallis test was used to assess group differences. Spearman correlational analysis was done to assess correlation between income, work experience and job satisfaction. Results: Significantly higher professional satisfaction, lower burnout and stress scores were observed in experienced healthcare workers as compared to less-experienced ones (p value =0.039* for JSS, p value =0.011* for CS, p value =0.055* for BO and p value =0.027* for STS). Significantly higher satisfaction scores were found in workers with higher monthly income as compared to those with lower monthly salary (p value =0.006* for JSS and p value =0.032* for CS). Significant positive correlation was observed between healthcare workers' job satisfaction and their experience and monthly salary. Conclusion: More experience at work is particularly associated with lower burnout and reduced occupational stress.